HUBUNGAN DESIRE DALAM AKTIVITAS SEKSUAL DENGAN HORMON PROGESTERON WANITA HAMIL TRIMESTER I, II DAN III - Arif Tirtana; Ova Emilia; Dicky Moch. Rizal (Jurnal Kesehatan Madani Medika (JKMM), 2018)
Pregnant women will produce higher hormone progesteron in each trimester (TM), this is intended to maintain pregnancy. One function of the progesterone hormone in maintaining pregnancy is the progesterone hormone as immunomodulator. The hormone progesterone can suppress the activation of NK cells in pregnant women. The hormone progesterone in women serves as a sexual drive that in stimulating the existence of sexual activity (Desire). The purpose of this study was to determine the relationship of desire with progesterone hormone in pregnant women TM I, TM II and TM III. The research design was cross sectional. Sample calculation on research based on correlation coefficient (r) using total sample size formula. Evaluation of desire using Female Sexual Function Index (FSFI) questionnaire. Different tests use Kruskal Wallis. Correlation test using pearson. The results of different desire test in pregnant women TM I, TM II and TM III were 0,250 (P> 0,005). Different test results of progesterone hormone in pregnant women of trimester I, II and III with result 0.000 (p